A serious game (immunitates) about immunization : development and validation study - Lima, Isabela Dantas de Araujo (2022)
Background: Vaccination is a fundamental part of all levels—local to worldwide—of public health, and it can be considered one of humanity's greatest achievements in the control and elimination of infectious diseases. Teaching immunization and vaccination can be monotonous and tiring. It is necessary to develop new approaches for teaching these themes in nursing school. Objective: We aimed to develop and validate a serious game about immunization and vaccination for Brazilian nursing students. Methods: We developed a quiz-type game, Immunitates, using design and educational theoretical models and Brazilian National Health Guidelines. The game’s heuristics and content were evaluated with 2 different instruments by a team of experts. A sample of nursing students evaluated the validity of the game’s heuristics only. We calculated the content validity index (CVI) for each evaluation. Results: The study included 49 experts and 15 nursing students. All evaluations demonstrated high internal consistency (Cronbach α≥.86). The game’s heuristics (experts: CVI 0.75-1.0; students: CVI 0.67-1.0) and the game’s contents demonstrated validity (experts: CVI 0.73-1.0). Participants identified some specific areas for improvement in the next version. Conclusions: The serious game appears to be valid. It is intended as a support tool for nursing students in the teaching–learning process and as a tool for continuing education for nurses.